Eksploitasi Tenaga Kerja dalam Ekosistem Ojek Online: Analisis Ketimpangan Sosial Perspektif Teori Kelas Karl Marx - Syifaul Qolbiyah (PROGRESIF: Jurnal Dakwah, Sosial, dan Komunikasi, 2026)
The rapid growth of the digital economy has transformed employment relations through platform-based work systems, including online motorcycle taxi services. Although previous studies have discussed the flexibility and economic opportunities offered by the gig economy, limited attention has been given to the issue of social inequality and labor exploitation within the online transportation ecosystem from the perspective of Karl Marx's class theory. This study aims to analyze the forms of social inequality experienced by online motorcycle taxi drivers and to explain the class relations that emerge between digital platform owners and workers. This research employs a qualitative approach using the literature review method. Data were collected from scientific journals, books, research reports, and relevant academic publications discussing the digital economy, gig economy, and Marxist social class theory. The collected data were analyzed through thematic content analysis. The findings reveal that online motorcycle taxi drivers occupy a vulnerable position as the digital proletariat, characterized by unstable incomes, dependence on platform algorithms, limited social protection, and exploitative incentive systems. Meanwhile, platform companies function as the digital bourgeoisie by controlling digital infrastructure and extracting surplus value from workers' labor. The study also identifies that the adoption of technological innovations, such as electric motorcycles, may create additional economic burdens for drivers rather than improving their welfare. This study contributes to the discourse on the digital economy by integrating the concept of platform capitalism with Marx's class theory to explain the structural inequality within Indonesia's online motorcycle taxi ecosystem. The findings highlight the importance of regulatory intervention and stronger labor protection policies to create a fairer and more sustainable digital economy.